Beyond the Lab: Empirically Supported Treatments in the Real World - Schneider, Renee A.; Grasso, Joseph R.; Chen, Shih Yin; Chen, Connie; Reilly, Erin D.; Kocher, Bob (Frontiers in Psychology, 2020)
Laboratory studies of empirically supported treatments (ESTs) for mental health problems achieve much higher rates of clinical improvement than has been observed following treatment in the community. This discrepancy is likely to due to limited reliance on ESTs by therapists outside of academia. Concerns about the generalizability of ESTs to patients in the community, who may have comorbid problems, likely limit rates of adoption. The present study examined the impact of ESTs delivered in the real-world for 1,256 adults who received services through an employee assistance program specializing in the delivery of ESTs. Rates of anxiety and depression decreased significantly, following treatment with an EST, and 898 (71.5%) patients demonstrated reliable improvement. Even among patients comorbid for depression and anxiety at baseline, over half reported reliable improvement in both disorders. Findings suggest ESTs can be effectively delivered outside of academic RCTs. However, additional research is needed to understand and overcome barriers to disseminating ESTs to the broader community.